Economic valuation analysis: Understanding the potential of agricultural land in the sustainable food agricultural land area in the Special Region of Yogyakarta Province, Indonesia - Harini, Rika; Puspitaningrum, Ismi; Sari, Vanessa Anggreta; Dairina, Isnaini (Journal of Degraded and Mining Lands Management, 2025)
The economic conversion of agricultural land often disregards its environmental significance, threatening food security and ecosystem integrity. This study evaluated the potential of agricultural land resources within the Sustainable Food Agricultural Land Area (LP2B) in the Special Region of Yogyakarta Province, Indonesia, by quantifying their total economic value (TEV) and developing strategic recommendations for sustainable land management. Utilizing a mixed-method approach based on secondary data and SWOT analysis, the research revealed that Bantul Regency is the regency with the highest total economic value of agricultural land, and Gunungkidul is the regency with the lowest total economic value, exhibiting high TEV due to its robust agricultural productivity and ecological functions. The study emphasized indirect benefits—including flood and erosion control—that are undervalued in current land-use decision-making. Strategic solutions such as digital agriculture initiatives and farmer regeneration programs are proposed to mitigate land conversion and bolster rural resilience. These findings provide actionable insights for policymakers aiming to balance economic development and environmental sustainability in rapidly urbanizing regions.